(untitled) (Cardiovascular Journal, 2014)
Background: Side branch occlusion is a well known complication of percutaneous coronary intervention. Although occlusion of small side branches is well tolerated, occlusion of larger side branches may cause more serious complications. After PCI the incidence of complications in patients with compromised side branches smaller than 2 mm is small. Compromising side branches larger than 2 mm can be accompanied by clinical outcomes as non Q-wave MI. This study was undertaken to assess the in-hospital outcomes of compromised small (<2mm) side branch after percutaneous coronary intervention. Methods: This cross sectional analytical study was carried out in the department of cardiology, National Institute of Cardiovascular Diseases, Dhaka during the period of September 2011 to June 2012. A total of 100 consecutive patients with coronary artery disease who underwent elective PCI were included in the study. Study patients were divided into two groups on the basis of presence of compromised small (< 2 mm) side branch. In Group- I, small (< 2 mm) side branch were compromised after PCI and in Group- II, side branches were patent after PCI, with 50 patients in each group. In-hospital outcome were evaluated in both groups. Result: There were no significant differences of the baseline clinical demographics between two groups. Post PCI angina was higher in group I than group II (10.0% vs. 9.0%). Non ST elevation myocardial infarction and significant arrhythmia was identical in both groups (2.0% vs. 2.0%) but hypotension was more in group II than group I (4.0% vs. 2.0%). The findings were statistically insignificant between the study groups. There was no mortality, emergency CABG within 24 hours, ST elevation myocardial infarction, cardiogenic shock or acute left ventricular failure during their hospital course in either group. Conclusion: The present study concluded that compromised small (<2mm) side branch after percutaneous coronary intervention was not associated with adverse in-hospital outcome. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20795 Cardiovasc. j. 2014; 7(1): 11-16